The relationship between financial knowledge, financial attitudes, financial planning and financial security among workers: A pilot study - Ab Rani, Nor Zuriati Amani; Nik Hassan, Nik Suriati; Zahari, Nor Sabrina; Mohd Hassan, Norsilawati; Mustafa, Tismazammi; Mat Nawi, Farahiyah Akmal (Journal of Islamic, Social, Economics and Development, 2026)
Financial literacy has become a critical determinant of individual economic well-being and national financial stability. The financial literacy is multidimensional, typically encompassing financial knowledge, financial planning and financial attitudes .This study examines the relationship between financial knowledge, financial attitudes, financial planning and financial security among workers. A pilot study was conducted involving 53 respondents from various occupational and income backgrounds. Descriptive statistics, correlation analysis and ANOVA were employed to analyze the study. The findings indicate that respondents demonstrate relatively high levels of financial planning (M = 3.98) and financial knowledge (M = 3.88), while financial attitudes recorded comparatively lower scores (M = 2.89). The correlation analysis reveals strong and statistically significant positive relationships among the main constructs. Financial planning exhibits a very strong association with financial knowledge (r = .802, p < .001) and financial security (r = .822, p < .001). These findings suggest that planning behaviour serves as a crucial mechanism translating financial knowledge into financial security outcomes. Policy implications emphasize the need for income-sensitive financial planning and behaviour reinforcement strategies to promote sustainable financial well-being.